2020
DOI: 10.3390/su12083358
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Efficient Method to Evaluate the Potential of Eutectic Solvents to Dissolve Lignocellulosic Components

Abstract: The application of eutectic solvents (ESs) in lignocellulosic biomass fractionation has been demonstrated as a promising approach to accomplish efficient and environmentally friendly biomass valorization. In general, ESs are a combination of two components, a hydrogen-bonding donor and a hydrogen-bonding acceptor, in which the melting point of the mixture is lower than that of the individual components. However, there are plenty of possible combinations to form ESs with the potential to apply in biomass proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…20 However, the study of lignin dissolution in DES, especially technical lignins from well-established delignification processes (e.g., kraft pulping), toward their further valorization is still barely examined. 21,22 Francisco et al 23 investigated a wide range of DES to dissolve low sulfonated kraft lignin and cellulose. The authors used carboxylic acids as HBDs, while alanine, betaine, [Ch]Cl, glycine, histidine, proline, and nicotinic acid were chosen as HBAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…20 However, the study of lignin dissolution in DES, especially technical lignins from well-established delignification processes (e.g., kraft pulping), toward their further valorization is still barely examined. 21,22 Francisco et al 23 investigated a wide range of DES to dissolve low sulfonated kraft lignin and cellulose. The authors used carboxylic acids as HBDs, while alanine, betaine, [Ch]Cl, glycine, histidine, proline, and nicotinic acid were chosen as HBAs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It can be seen from Table 2 that among the tested and reported DESs, 17 LA : ChCl in the ratio of 10 : 1 was an excellent solvent for AL and a commonly used DES for biomass pretreatment. 12,[22][23][24] Therefore, LA-ChCl (LA : ChCl 10 : 1) was chosen as the DES to dissolve AL.…”
Section: Resultsmentioning
confidence: 99%
“…These features drew attention to apply DESs in lignin dissolution 30 and biomass delignification. 31,32 Several studies have reported acidic DESs, such as those formed by the combination of cholinium chloride ([Ch]Cl) as a HBA and carboxylic acids, including oxalic acid (Oxa), formic acid (For) and lactic acid (Lac) as a HBD, as efficient solvents for the extraction and dissolution of lignin from biomass.…”
Section: Introductionmentioning
confidence: 99%